Effect of Natural Fibers from Palm Fronds on The Mechanical Properties of Concrete - Mouthanna, Alhareth (Anbar Journal of Engineering Sciences, 2022)
Scientists have recently started looking for new ecologically friendly and sustainable materials. Construction materials are among the numerous widely employed materials, and it is normally acknowledged that they have an apparent detrimental influence on the environment. Thus, the contribution of this paper is to describe the palm frond natural fibers’ effect on concrete’s mechanical characteristics. Since concrete is a brittle material, the goal of this research is to increase the tensile strength of concrete by using organic fibers (palm frond fibers), a waste product. In order to determine the ideal percentage of fibers, the following percentages were tested: 0.25, 0.5, 0.75, and 1% by volume of concrete. On dry density, compressive strength, and tensile strength, the impacts of fibers were investigated. The density of concrete decreased with increasing fiber ratios. The compressive strength slightly decreased, while the splitting strength significantly improved. According to the results, the best amount of palm frond fibers that can be add to concrete is 0.75% by volume.